Controlling The Radiation Pattern of Patch Antenna Using Switchable EBG - M.K. Abdulhameed; M.S. Mohamad Isa; Z. Zakaria; M.K. Mohsin (Universitas Ahmad Dahlan, 2018)
The advantages of the beam steering technique are the reduction of interference, save power and to maximize connectivity for point to multi points. Antenna gain degradation is a big problem in the beam steering technique. A new antenna structure is formed by combining the concept of mushroom-like EBG structure with the switching diode to produce the radation pattern control. All sides of the patch antenna are surrounded by several cells for EBG structure. In both of the the left and right sides, through a switching pin diode, the ground plane is attached to vias. The band-stop and band-pass properties of the EBG sector can be changed with the help of switching the diode between ON and OFF state, thus yielding the beam steering into that particular sector. At 6 GHz operational frequency, this structure has the ability to steer 40º (from -20º to +20º) while minimal diodes are utilized, directivity of 10 dBi, gain 9.86 dB and the efficiency is 96.5%. This approach is robust to gain degradation and the main lobe gain is approximately constant for all steering angles.